AIRCRAFT NAVIGATION EFFICIENCY IMPROVING DURING LANDING USING SATELLITE NAVIGATION SYSTEM - Kharchenko, Volodymyr; Konin, Valeriy; Olevinska, Tetiana (Proceedings of National Aviation University (archive), 2017)
Purpose: Two algorithms have been considered in this article. Both of them make possible to improve aircraft navigation efficiency during landing by satellite navigation system signals. The first algorithm describes creation of two reference planes in space using measured coordinates of four points on the runway and the subsequent calculation of the aircraft horizontal and vertical angular deviation from these planes. The second algorithm describes an autonomous integrity control in the aerodrome area when four satellites are visible. Methods: methods of experiment planning, analytic geometry and linear algebra have been used. Results: obtained a new experimental data. Discussion: The results of experimental research of the first algorithm showed the principal possibility of deviation calculation in this way. It is shown that implementation of this technology will make it possible to increase the efficiency of small aircrafts navigation during landing at aerodromes and landing areas that are currently not equipped with radio equipment for instrument landing. The results of research of the second algorithm showed that it allows reducing the number of satellite navigation system failures and also enhances navigation efficiency. These results can be used in the aerospace sector for reducing the number of small aircraft non-flying periods.